2015
DOI: 10.1038/srep12964
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced thermal properties of novel shape-stabilized PEG composite phase change materials with radial mesoporous silica sphere for thermal energy storage

Abstract: Radial mesoporous silica (RMS) sphere was tailor-made for further applications in producing shape-stabilized composite phase change materials (ss-CPCMs) through a facile self-assembly process using CTAB as the main template and TEOS as SiO2 precursor. Novel ss-CPCMs composed of polyethylene glycol (PEG) and RMS were prepared through vacuum impregnating method. Various techniques were employed to characterize the structural and thermal properties of the ss-CPCMs. The DSC results indicated that the PEG/RMS ss-CP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
119
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 215 publications
(123 citation statements)
references
References 38 publications
4
119
0
Order By: Relevance
“…On the other hand, silica has been extensively investigated in the fields of PCMs and heat storage. Berthou [23] has formed a new translucent passive solar wall by combining silica aerogels and PCMs; Min [2] has investigated PEG/mesoporous-silica-shape-stabilized PCMs; Chen [24] has utilized hydrophobic fumed silica for preparing form-stable composite PCMs; Qian [5] and He [25] have prepared shape-stabilized PEG/SiO 2 composites by sol-gel methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, silica has been extensively investigated in the fields of PCMs and heat storage. Berthou [23] has formed a new translucent passive solar wall by combining silica aerogels and PCMs; Min [2] has investigated PEG/mesoporous-silica-shape-stabilized PCMs; Chen [24] has utilized hydrophobic fumed silica for preparing form-stable composite PCMs; Qian [5] and He [25] have prepared shape-stabilized PEG/SiO 2 composites by sol-gel methods.…”
Section: Introductionmentioning
confidence: 99%
“…With rapid development in economy, science and technology, non-renewable resources are continuously being exhausted, energy issues have become a "bottleneck" in the economic and industrial development [1]; for these reasons, the utilization of renewable energy sources is receiving increasing attention among researchers, worldwide [2,3]. It is imperative to closely monitor phase change materials (PCMs) used for storing thermal energy [4].…”
Section: Introductionmentioning
confidence: 99%
“…Min et al 19 managed to enhance the thermal properties of shape-stabilized PEG composite PCMs with radial mesoporous silica spheres. He et al 20 used calcium chloride-assisted and temperature-assisted sol-gel methods to developed shapestabilized PEG/SiO 2 composite materials, and the DSC and TGA data showed that PEG/SiO 2 had the appropriate phase change temperature and good thermal stability to solve the leakage problem of melted PEG.…”
Section: Introductionmentioning
confidence: 99%
“…22 Fang et al successfully used silicon dioxide or silica shell to stabilize nhexadecane, 23 lauric acid, 24 and octadecane, 11 respectively, and the thermal storage capacities of the prepared composite PCMs were 100-230 J g…”
Section: 1114-21mentioning
confidence: 99%
“…The thermal storage capacities of the prepared composite PCMs were 50-90 J g À1 and they were useful for applying to building materials. Min et al 22 for the rst time used the radial mesoporous silica to support polyethylene glycol, and their thermal storage capacities were 60-120 J g À1 with different contents of PEG. Song et al 28 used the silica shell microencapsulated caprice-stearic acid with a thermal storage capacity of 91.48 J g À1 while the encapsulation ratio was 56.7 wt%, and prepared composite PCMs showed good thermal reliability.…”
mentioning
confidence: 99%